PELATIHAN KOMUNIKASI EFEKTIF DALAM PEMBELAJARAN DARING MELALUI GOOGLE CLASSROOM PADA GURU DI SD NEGERI 204 KERTAPATI PALEMBANG - Sulistijanto, Andi Budi; Anita, Sumarni Bayu; Bayumi, Ruli Ihsan (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2021)
This activity aims to train effective communication for teachers at SDN 204 Kertapati Palembang with students. Informants activities of teachers and students. Data collection was obtained through interviews, observations, documentation, to informants. Meanwhile, the analysis approach is carried out with a qualitative approach. Based on the results, the teachers began to understand the training and quite understand the online learning process through Google Classroom. At SDN 204 Kertapati, the role of teachers' communication and social change, which was originally face-toface learning, had to switch to online or dare to be carried out by all teachers involved in the bold learning process. The home study system really needs communication and significant social changes in this pandemic situation. The teacher's role in assisting children to learn during the COVID-19 pandemic is going well, although there are factors that hinder the implementation of online learning obtained during training at SDN 204 Kertapati, according to the teachers, it is difficult for their students to understand the material because they are not accompanied directly by the brave medium. The next obstacle is parents when accompanying their children to study impatiently, internet service constraints, and the limitations of cellphone media as a learning medium for students.